89 Primary Cilia In Tenocytes From The Inter-fascicular Matrix And The Fascicular Matrix. (5th September 2014) - Rowson, Daniel; Knight, Martin; Screen, Hazel
Abstract : Introduction: Primary cilia are eukaryotic organelles found singularly on almost every cell in the body. Primary cilia localise a number of developmental signalling pathways, and for some of these pathways, the rate of signalling is dependent on cilia length (Thompson et al . 2014). Tenocytes have previously been shown to have primary cilia, which increase in length when tendon is stress deprived (Gardner et al . 2011). The cilia within fascicles have also been shown to orient in the direction of applied load (Donnelly et al . 2010). Recent work from our group suggests two distinct populations of cells within tendon; those in the inter-fascicular matrix (IFM) or epitendon (IFM cells), and those in the fascicular matrix (FM cells). Preliminary data suggests IFM cells experience different strain fields to FM cells, and may also be more metabolically active. We therefore hypothesise that there will be a difference in the length of the primary cilia in IFM and FM cells under physiological strain conditions, and cilia orientation will also differ between cell types in relation to their different strain conditions. Further, we hypothesise that stress deprivation will result in a greater increase in primary cilia length in the more metabolically active IFM cells. Materials and methods: Tails were collected from two 200 g female Wistar rats killed for unrelated reasons. From each tail, 4–6 fascicles were dissected and immediately fixed, whilst an additional 4–6 fascicles were dissected and incubated in media for 7 days in a stress deprived condition, prior to fixing. The fixed fascicles were fluorescently labelled using the antibody arl13b, a cilia specific membrane protein. A series of images 0.25μm apart in the z-plane were taken, either at a depth 20–40μm into the FM or through the entire thickness of the IFM. Images were taken using a Leica scanning confocal microscope, using a x63 lens and reconstructed into a 3D z-stack using imageJ. Cilia length and orientation was measured in 3D, using image J (n = 5–30/fascicle). Results: Considering the fresh fixed samples, the primary cilia of IFM cells were significantly longer than those of FM cells in one rat tail (IFM = 1.8 ± 0.52 μm; FM = 1.4 ± 0.46 μm; p < 0.001), whilst the second tail showed no significant differences. After stress deprivation, the primary cilia of both cell populations were significantly longer than seen in the fresh tendon. However, the increase in length was significantly larger in the IFM cells, shown in Figure 1 . In both rats, FM cell cilia were consistently aligned parallel to the tendon loading axis, as seen previously (Donnelly et al . 2010). However, the cilia of IFM cells were predominantly located in alignment with the boundary between the IFM and FM, but in multiple directions relative to the tendon loading axis. Discussion: Cilia length and orientation are different in the IFM and FM. The strain environments of these two regions differ, and FM cells are thought to experience combined tensile and shear strains, while IFM cells may experience primarily shear. This may explain the increased length of IFM cell cilia, as previous data indicates that tensile strain shortens cilia (Gardner et al . 2011). Shear strains within the IFM will be lowest at the boundary between the IFM and FM; where IFM cell cilia were located. It may be that the cilia are localised in this region to minimise the shear strain they experience. References: Donnelly, et al . J Orthop Res . 2010;28;77–82 Gardner, et al . J Orthop Res . 2011;29(4);582–7 Thompson, et al . OARS. 2014;22(3);490–8